VD_FINDINFO HC / 2014 / 750 vom 25. August 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, CONJOINT, ENFANT, PROTECTION DE L'UNION CONJUGALE | 176 al. 1 CC, 176 al. 3 CC, 276 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)